Brand Image and E-WOM: Antecedents of Green Marketing on E-commerce Users' Purchase Decisions - Faiza, Nur; Rachman, Riza; Wahyuni, Alfi; Wulandari, Dewi; Agustin, Hamdani Eldafiyah (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Green marketing is an essential strategy in promoting public awareness of sustainability and the green economy. A positive brand image and strong e-WOM can influence consumer purchasing decisions in e-commerce. Environmentally friendly products are increasingly becoming the choice in supporting economic sustainability in the future. However, the effectiveness of green marketing in driving purchasing decisions through brand image and e-WOM still needs further analysis. The purpose of this study is to analyse the direct and indirect effects of green marketing on purchasing decisions, with brand image and e-WOM as mediators, among consumers who buy green products in Situbondo Regency. Hypothesis testing was conducted based on a structural equation model using the Partial Least Squares (SEM-PLS) approach. The main achievement expected from this study is to fill the knowledge gap by exploring how brand image and e-WOM can strengthen the influence of green marketing on purchasing decisions, particularly among electric bicycle users in Situbondo Regency. The results of this study can be used as a consideration in formulating more effective green marketing strategies by maximising the roles of brand image and e-WOM to encourage purchasing decisions.